Consistency checking of UML business model - Vasilecas, Olegas; Dubauskaitė, Rūta; Rupnik, Rok (Technological and Economic Development of Economy, 2011)
Unified modelling language (UML) is often used in practice for modelling business system (BS) by various aspects. UML model of business system consists of different aspect models and their usage for information system (IS) design is related with inconsistency problem. It arises because ambiguous or even contradictory information are provided in different aspect models. The paper presents approach in ensuring UML model consistency. Several examples of consistency rules are included to the paper to illustrate how approach is working. Developed prototype of suggested approach is applied in a domain of enterprise manufacturing windows and doors. Obtained results are discussed.